PELAKSANAAN BIMBINGAN ROHANI ISLAM UNTUK MEWUJUDKAN PELAYANAN PRIMA DI PERPUSTAKAAN DAERAH PROVINSI SUMATERA BARAT: Pelaksanaan Bimbingan Rohani Islam Untuk Mewujudkan Pelayanan Prima Di Perpustakaan Daerah Provinsi Sumatera Barat - Eli Nelpita; Ulfatmi Ulfatmi; Juliana Batubara; Hamzah Irfanda Irfanda (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study is motivated by the existence of a distinctive religious program at the West Sumatra Provincial Public Library, namely Islamic spiritual guidance. This program serves as a relevant strategy for fostering spiritual and moral awareness, particularly among library staff, which in turn supports the improvement of service quality. The research employed a descriptive qualitative approach with a field research design. The purpose of this study was to describe and analyze: (1) the planning of the Islamic spiritual guidance program to enhance excellent service at the West Sumatra Provincial Public Library; (2) the implementation of the program in improving excellent service; (3) the evaluation of the Islamic spiritual guidance program in strengthening excellent service performance; and (4) the challenges and obstacles encountered during the implementation of the program. The findings reveal that: (1) the planning of the Islamic spiritual guidance program constitutes a series of strategic steps aimed at improving the quality of excellent service among library staff; (2) the implementation of Islamic spiritual guidance functions as an effort to enhance excellent service by cultivating religious values and positive work ethics among library employees; (3) the evaluation indicates that the Islamic spiritual guidance program is relevant and effective in establishing a superior service culture grounded in Islamic values, and therefore deserves to be sustained and further developed as part of the library’s service quality improvement strategy; and (4) although the implementation of Islamic spiritual guidance faces various challenges and obstacles, overcoming these issues enables the program to run more effectively and provide optimal benefits for library users, ultimately contributing positively to the improvement of excellent service quality at the West Sumatra Provincial Public Library.